ORANGUTAN (Pongo pygmaeus ssp. wurmbii) RANGING PATTERN IN PUNGGUALAS, SEBANGAU NATIONAL PARK, CENTRAL KALIMANTAN INDONESIA: Ranging pattern of P.p. wurmbii in Punggualas, Sebangau National Park - Adventus Panda; Ari Meididit; Okta Simon; Wayan Tunas Artama; Dwi Priyowidodo; Tjut Sugandawaty Djohan (SEAMEO BIOTROP, 2023)
Punggualas lies in the western part of Sebangau National Park (SNP). It is a logged-over forest, yet it is one of the major strongholds for the P. p. wurmbii population in the SNP. The range size, as well as the ranging pattern for Punggualas, has never been conducted. The study aimed to estimate orangutan ranging size and pattern as well as their distribution over the Punggualas forest. Ranging data within the area of interest (AOI) was collected from Feb 2015 – Dec 2019 (P1), and Mar 2020 – May 2022 (P2). Minimum convex polygon (MCP), range size of orangutan individual was calculated using adehabitatHR package in RStudio 4.1.1 for Windows. We visualized the distribution in ArcGIS 10.5 with Kernel Density (KD) tool. The range size of Mother-Infant is the greatest (259,6 Ha) among all individuals being studied within the study periods. Moreover, the size estimation was found greater in Mother-Infant sex class compared to other orangutan studies areas, such as Peat Natural Laboratory, and CIMTROP-UPR which reported a flanged male HR Size reaching 250 Ha per annum. We have found that the ranging pattern significantly changes over the study period. However, during P1, the distribution area was located within the northern of AOI, while in the P2 have changed to the south-eastern part of the AOI. We concluded that the ranging pattern indeed follows the fruit availability as well as fine-scale habitat quality.